Penyelesaian Sengketa Wanprestasi Debitur Dalam Perjanjian Sewa Menyewa Rental Mobil (Studi Kasus Rent Car Professional) - Wira Nanda, Rahmat; Yadi Harahap, Mhd. (UNES Law Review, 2023)
Legal provisions regarding leasing as regulated in article 1548 of the Civil Code which reads "An agreement, by which one party binds himself to provide the enjoyment of an item to another party for a certain time, with the payment of a price that the latter party can afford" , by which one party binds himself to give the other party the enjoyment of an item, for a certain time and payment of a price, which the latter party has agreed to pay. Therefore, a legal relationship arises, namely a vehicle rental agreement. It was then explained that the length of the lease depends on the agreement by both parties as outlined in the contents of the agreement as regulated in Article 1338 paragraph (1) B.W., which reads: "All agreements made legally apply as law for those who make them". Debtor default disputes in car rental rental agreements are examined by the legal relationship between the parties involved. This research uses an empirical juridical legal research approach in analyzing problems that have been formulated by combining both primary and secondary legal materials. The results of this research are to find out further processes in resolving Debtor default disputes in car rental rentals. The designation of the parties in a car rental lease is usually for the renting party to be called the debtor and the renting party as the creditor. If there is a dispute over non-compliance with the rental car rental, this will be done through deliberation/peace (non-litigation) by the creditor and debtor.